THE ROMANI IN THE MACEDONIAN EDUCATIONAL SYSTEM - Dushka Matevska (TRAKYA UNIVERSITY - EDIRNE, 2018)
Education is an individual right and necessity in modem society. Education has, value in itself, independently of the economic value it brings to the individual, or the lack there of, because it enriches all individuals and it enables meaningful orientation in the world. The analysis of the Macedonian educational structure shows that half of the population that is 15 or older doesn't possess or possesses a low level of education. It is especially concerning that we have a larger percentage of illiterates in rural municipalities and municipalities where certain minorities such as Albanians, Turks and Romani dominate, Macedonia, as a multiethnic society, has defied the rights and freedoms or the national minorities in article 48 of the Constitution from 1991, according to which, they have the right to freely express, nurture and develop their identity, as well as the right to tuition in their native language in primary and secondary school. However, the tuition in their native tongue isn't implemented equally for all minorities. Primary school education, which is compulsory in Macedonia, has tuition in Macedonia us well us Albanian. Serbian and Turkish, while the Romani population is far from realizing their right to tuition in their native language even though they are the third most numerous minority in Macedonia. From all the present minorities, only the Turkish populace has secondary school tuition in their native tongue, despite the fact that the 2007 changes to the law of secondary education implemented compulsory secondary education to all citizens, with equal opportunities. In this paper we will try to detect the reasons for the low achievements and high dropout rates of Romani children. According to the State Statistical Office a small percentage of enrolled Romani children finish primary school. There are many obstacles they face which make it difficult for them to succeed in our education system, The combination of poverty and a specific subculture keeps the Romani populace in the "magical circle of poverty" . The low level of education and vocational training lower the chances of successful integration in society and leads to higher vulnerability and discrimination, Macedonia shouldn't rely on passive or repressive measures to include Romani in the educational process but should develop a strategy of positive measures that will bring education closer to the Romani people. Till now, the Romani people had to adapt to the way of life of the larger communities. where the proper help wasn', offered even though they are the poorest and most vulnerable community. Special attention needs 10 be paid to the tradition and values that are nurtured ill Romani culture, and a way to strengthen education as a ",due .md coveted goal in Romani culture needs to be devised,
Keywords: educational system, educational opportunities, Romani culture